THE SURFACE-TENSION OF CORK FROM CONTACT-ANGLE MEASUREMENTS - GOMES, CMCPS; Fernandes, A C; DEALMEIDA, B D (JOURNAL OF COLLOID AND INTERFACE SCIENCE, 1993)
The surface tension of cork is evaluated from contact angle measurements in cork-water-air and cork-methylene iodide-air systems, using the geometric and the harmonic mean methods. The contact angles were studied as a function of time and, in each case, the extrapolated value for t = 0 was used in the calculations to obtain γs. In spite of the chemical and physical complexity of cork, it was possible to obtain an average value for its surface tension γs = 32 ± 3 dyne cm-1 and polarity γPS/γS= 0.25. These values were compared to others obtained for several natural products such as wood or cellulose derivatives.
APS
Keywords: chemical complexity; geometric method; harmonic method; physical complexity